IMPROVEMENT OF THE WORKING PARTS OF COTTON CLEANING EQUIPMENT - Ergashev , Yuldashali; Marifxonov, Boxodirxon Ulugʻbek oʻgʻli (Educational Research in Universal Sciences, 2023)
The improvement of working parts in cotton cleaning equipment is crucial for enhancing the efficiency of the gin process. This article explores the significance of optimizing the working parts of cotton cleaning equipment, focusing on the components, maintenance, and advancements in technology. By implementing these improvements, cotton processing facilities can elevate productivity, reduce maintenance costs, and enhance the overall quality of cotton output.